Tasks for service modularization planning - Ilona Skačkauskienė; Jurga Vestertė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Service modularization is gaining increasing attention from scholars and practitioners. However, it must be noted that the essence of service modularization is still not well understood, and its purposefulness of practical application has not yet been well explored. This conceptual paper presents the results of ongoing research addressing service modularization planning issues. The study examines the relationships between the premises and the outcomes of service modularisation. Based on the obtained results, the authors provide the purpose statement for service modularisation. Further, the work outlines the activities that are critical to planning as a management function, analyses their content in the context of service modularization, and identifies the problems that require management decisions. The paper employs comparative analysis, systemic analysis, abstraction, synthesis, abductive reasoning for achieving the research results.
Keywords: M11; 650; service modularization; service planning; planning decisions; service quality; service customization; service standardization